PENERAPAN PEDOMAN PERILAKU HIDUP BARU DALAM PENCEGAHAN DAN PENGENDALIAN COVID-19 DI KOTA PEKANBARU - Nurrahmad Pebriansyah; Febri Yuliani; Adianto Adianto (Journal Publicuho, 2021)
The purpose of this study is to explain how the municipal government of Pekanbaru provides guidelines that should be carried out by the community in carrying out activities in Pekanbaru. This research uses qualitative research methods. The selection of research informants used perposive sampling technique. Primary data collection from interviews, while secondary data from documentation and literature study. Data analysis using an interactive model. The results showed that the application of new life behavior guidelines based on the Mayor of Pekanbaru regulation number 104 of 2020 concerning guidelines for new productive and safe lives in the prevention and control of Coronavirus Desease 2019 (Covid-19) in Pekanbaru has paid attention to the lives of its people, it can be seen from its existence. Guidelines for carrying out activities and activities during the Covid-19 pandemic. However, there is still an increase in positive cases of Covid-19 due to people who do not comply with applicable policies. For this reason, the municipal government of Pekanbaru needs to reaffirm people who commit violations so that they can comply with health protocols, especially in crowded places.